Epigenetic regulation of cardiac electrophysiology in atrial fibrillation: HDAC2 determines action potential duration and suppresses NRSF in cardiomyocytes - Lugenbiel, Patrick; Govorov, Katharina; Syren, Pascal; Rahm, Ann-Kathrin; Wieder, Teresa; Wunsch, Maximilian; Weiberg, Nadine; Manolova, Emili; Gramlich, Dominik; Rivinius, Rasmus; Finke, Daniel; Lehmann, Lorenz; et al. (Basic research in cardiology, 2021)
Atrial fibrillation (AF) is associated with electrical remodeling, leading to cellular electrophysiological dysfunction and arrhythmia perpetuation. Emerging evidence suggests a key role for epigenetic mechanisms in the regulation of ion channel expression. Histone deacetylases (HDACs) control gene expression through deacetylation of histone proteins. We hypothesized that class I HDACs in complex with neuron-restrictive silencer factor (NRSF) determine atrial K+ channel expression. AF was characterized by reduced atrial HDAC2 mRNA levels and upregulation of NRSF in humans and in a pig model, with regional differences between right and left atrium. In vitro studies revealed inverse regulation of Hdac2 and Nrsf in HL-1 atrial myocytes. A direct association of HDAC2 with active regulatory elements of cardiac K+ channels was revealed by chromatin immunoprecipitation. Specific knock-down of Hdac2 and Nrsf induced alterations of K+ channel expression. Hdac2 knock-down resulted in prolongation of action potential duration (APD) in neonatal rat cardiomyocytes, whereas inactivation of Nrsf induced APD shortening. Potential AF-related triggers were recapitulated by experimental tachypacing and mechanical stretch, respectively, and exerted differential effects on the expression of class I HDACs and K+ channels in cardiomyocytes. In conclusion, HDAC2 and NRSF contribute to AF-associated remodeling of APD and K+ channel expression in cardiomyocytes via direct interaction with regulatory chromatin regions. Specific modulation of these factors may provide a starting point for the development of more individualized treatment options for atrial fibrillation.
Gesehen am 06.04.2021